PENGARUH PROFITABILITAS, LEVERAGE, DAN MODAL KERJA PADA NILAI PERUSAHAAN DENGAN CSR SEBAGAI VARIABEL INTERVENING - Atmaja, I Gusti Ngurah Yoga Dimas; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 24 No 1 (2018), 2018)
Companies are a group of people who are members of an organization that works to achieve certain goals. One of the company's most fundamental goals is to gain maximum profit or profit from its business activities. The purpose of establishment of a company not only to achieve maximum profit, but also aims to improve the prosperity of parties related to corporate activities, such as shareholders and stakeholders so that the value of the company increases. The purpose of this study is to determine the effect of profitability, leverage, and working capital on corporate value with CSR as intervening variable. This research is conducted in consumer goods company listed in Indonesia Stock Exchange (IDX) period 2013-2015 period. The number of samples taken as many as 75 companies, with purposive sampling method. Data collection is done by downloading the company's annual report. Analytical techniques used include regression analysis that requires descriptive statistics, classical assumption test, path analysis, and test sobel. Pursuant to result of path analysis and sobel test found that profitability and leverage not have an effect on CSR, while working capital have positive effect on CSR. Profitability affects positively on firm value, while leverage and working capital have no effect on firm value. CSR can not mediate the effect of profitability, leverage, and working capital on firm value.